The Cononodont Trapezognathus Diprion (Lindström) in the Acoite Formation, Eastern Cordillera, Northwestern Argentina - Carlorosi, Josefina Maria Teresa (2013)
This work is developed in NW Argentina framed in the geological province of the Eastern Cordillera, characterized by a set of siliciclastic outcrops mainly related to the Cambrian and Ordovician periods. The main purpose of this study focuses on the vertical distribution of the conodont Trapezognathus diprion (Lindström) recorded from the uppermost part of the Acoite Formation (Lower Ordovician), outcropping in three key areas where this formation was described: La Ciénaga, Espinazo del Diablo and Los Colorados.